Análise da tradução de termos na legenda profissional e na legenda de fãs do seriado Orphan Black - Mello, Maria Paula Silva (2018)
Orphan Black is a TV series which addresses issues of Biotechnology, in particular Cloning. This senior thesis analyzes the terminology from the original English audio/subtitle and its respective translation in the Portuguese-language professional subtitle and fan-made subtitle. The aim is to assess the degree of “equivalence” between the terms of the source audio and the target subtitles, the recurrence of these terms in the Biotechnology domain, as well as the similarities and differences between the translation options realized in the Portuguese-language subtitles. To this end, a parallel corpus was compiled containing three subtitles (original audio/subtitle, professional subtitle, and fan-made subtitle), and a criterion was adopted for the selection of the terms that would be analyzed, on which these would have to occur in a list composed by the entries of a specific Cloning glossary present in the National Research Council's Scientific and Medical Aspects of Human Reproduction Cloning (2002). The degree of “equivalence” was investigated based on Dubuc (1985). The results pointed out that contrary to expectation, the professional subtitle did not have more terminological consistency than the fan-made subtitles.